Clinical outcomes of proximal medial gastrocnemius release in the treatment of non-insertional Achilles tendinopathy - Sanhudo, José Antonio Veiga; Piccinin, Gabriele Elisete; Pancotto, Deise (Journal of the Foot & Ankle, 2025)
Objective: To evaluate the outcomes of proximal medial gastrocnemius release (PMGR), a procedure with relatively low morbidity, in the treatment of non-insertional Achilles tendinopathy. Methods: Twelve patients diagnosed with non-insertional Achilles tendinopathy, confirmed by clinical examination and nuclear magnetic resonance imaging, and refractory to conservative treatment, were treated with PMGR. Five patients had bilateral involvement, totaling 17 tendons treated. Results: After a mean follow-up of 32 months, the mean American Orthopaedic Foot and Ankle score increased from 62.1 preoperatively to 90.2 at last follow-up. The mean pain score on the visual analog scale decreased from 6.7 preoperatively to 1.9 at last follow-up. While some patients experienced residual pain, it was milder than preoperative pain in all cases, and all participants reported satisfaction after the treatment. Conclusion: Despite the small sample size and short follow-up period, the results were promising. As PMGR is a relatively simple procedure compared to tendon reconstruction techniques, it may be an attractive alternative treatment for this common and disabling disorder. Evidence Level: III; Type of Study: Retrospective study